"Effect of nitrogen content on properties of natural rubber coagulated by papain" - ZHANG Gui-mei, JIANG Shi-kuan, YAN Li, ZHU Ao, ZOU Jian-yun (Hecheng xiangjiao gongye, 2023)
Natural rubber with different nitrogen content (NR-P) was prepared by coagulation from fresh hevea latex with papain as granulation agent. The physical and chemical properties, curing cha-racteristics, physical and mechanical properties, compression fatigue heat build-up and dynamic mechanical properties of NR-P were studied and compared with that of acid-coagulated natural rubber (NR-A).The results showed that with decrease of nitrogen content, the initial plasticity of NR-P decreased first and then leveled off, while the plasticity retention index decreased slightly. The curing rate of the rubber compound with NR-P became faster, the modulus at 300%, tensile strength first increased and then decreased slightly. Besides, the heat build-up and rolling resistance of natural rubber vulcanizate also showed a decreasing trend. Compared with NR-A, the nitrogen content of NR-P was lower, but the initial plasticity was higher and plasticity retention index was slightly lower, and the curing rate and tensile strength were also better than that of NR-A. When the mass fraction of nitrogen of natural rubber was in the range of 0.18% to 0.23%, NR-P compounds exhibited faster curing rate, better mechanical properties, lower compression fatigue heat build-up and dynamic mechanical properties.